Efficacy of Antioxidant Supplementation to Non-Surgical Periodontal Therapy on Metabolic Control in Type 2 Diabetes Patients: A Network Meta-Analysis - Elisa Grillo Araújo; Domitilla Marchiori Sant'Anna Leal de Oliveira; Carolina Castro Martins; Cristine Miron Stefani (MDPI AG, 2022)
This network meta-analysis (NMA) investigated the effectiveness of antioxidants as adjuncts to non-surgical periodontal therapy (NSPT) in the glycated hemoglobin (HbA1c) control of type 2 diabetes (T2D) patients with periodontitis. PubMed, Cochrane, LILACS, Web of Science, Scopus, Embase, LIVIVO, and grey literature were searched. Risk of bias was assessed with the RoB v2.0 tool. A frequentist NMA assessed HbA1c improvement, through standardized mean difference under a random-effects model. Certainty of evidence was addressed through the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) partially contextualized framework. Ten randomized controlled clinical trials were included, with 234 patients receiving alpha lipoic acid (ALA), cranberry juice, cranberry juice enriched with omega-3, fenugreek, ginger, grape seed, lycopene, melatonin, omega-3, propolis or vitamin C supplementation to NSPT, and 220 patients receiving NSPT alone or with placebo. Nine studies were meta-analyzed. HbA1c improved when NSPT was combined with propolis, ALA and melatonin supplementation (moderate-to-low certainty), compared to NSPT alone or with placebo. Risk of bias issues were found in eight studies. In conclusion, the use of propolis supplementation to NSPT probably results in HbA1c improvement in T2D patients with periodontitis (large effect with moderate certainty), while ALA and melatonin supplementation may contribute to reduce the HbA1c in T2D patients with periodontitis (large effects with low certainty).